THE EFFECTIVENESS OF ONLINE EDUCATION IN DEVELOPING WRITING SKILLS - Karimberganova Shahnoza Muxammad qizi; Ruzmetova Diana Kamilovna (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract: This paper discusses how online education contributes to enhancing the writing skills of second language learners. With the rapid development of digital technologies, writing instruction has gradually moved from the traditional classroom- based approach to virtual learning environments. This article focuses on the advantages, limitations, theoretical backgrounds, technological tools, feedback mechanisms, and psychological factors that influence the process of online writing development. The findings of research suggest that online education may lead to significant improvement in the writing proficiency of learners if it is supported by structured feedback, collaborative tasks, and digital literacy. However, its pace might be hampered by limitations including reduced teacher presence, loss of motivation, and some technical issues. This paper concludes that online education works very effectively when supported by sound instructional design.